Identification of Facebook posts on nephrology-related terms that benefit patient outreach - Abdullah, Rafidah; Zakaria, Nor Fadhlina; Mushahar, Lily; Yakob, Suryati (Sage Journals, 2023)
Objective: The impact of social media on public health has been examined in various studies. However, none have explored user engagement based on the type of Facebook posts related to renal disease. Therefore, the present study sought to determine which type of nephrology-related posts have greater user engagement. Setting: Facebook pages. Methods: The posts on a specific Facebook page curated by a team of nephrologists in Malaysia were examined in this cross-sectional study. The type of post, likes, comments, shares of a post and reach of a post were used for data analysis. Analysis of variance was used to quantify the relative contribution of each independent variable to the odds of the post being highly liked or shared. The Kruskal-Wallis test was used to compare links, photos, shared videos, status and videos for parameters such as reach, the number of times a specific piece of content has been displayed on a screen (impressions), and user engagement. Results: Shared videos and photos received the highest median reach of 5,862 and 5,880, respectively. People who ˜liked the page in 2019, 2020 and 2021 numbered 193, 4,196 and 2,835, respectively. Among the types of content on the Facebook page, photos and shared videos received the highest median lifetime reach of the post compared to links, status and videos in terms of 'people who 'liked' the page. Conclusion: The study findings suggest that posting a video or photo maximises the chance of engagement and meaningfully impacts public health outcomes.